Avicennia officinalis L. - A Promising Source for The Creation of Medicines for Hepatoprotective and Antioxidant Activities in HepG2 Cell Line and Mice - Duong, Tuyet-Ngan; Nguyen, Ngoc-Van Thi; Nguyen, Ngoc-Anh; Do, Hong-Tuoi Thi; Le, Kim-Anh Thi; Dai, Xuan-Trang Thi; Duong, Cao-Duy; Thang, Truc-Ly Thi; Le, Huynh-Duc; Huynh, Mai-Tram Thi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Avicennia officinalis L. (AOL), a mangrove plant, is extensively used as an anti-inflammatory, anti-cancer, and antioxidant which has traditionally utilized this plant as herbal in Vietnam. In preliminary phytochemical screening, the methanol and aqueous leaf extracts showed high levels of bioactive compounds including glycosides, saponins, flavonoids, tannins, and triterpenes. To identify the major compounds in five extracts of AOL (leaves, flowers, fruits, roots, and bark), the quantitative HPLC/PDA technique was utilized. It was discovered that the total flavonoid content and total phenolic content were 52.55±0.070 and 16.59±0.030 mg/g extract, respectively. The result of antioxidant activity in vitro was shown leave and bark extract with the strongest activity (citric acid aqueous leave with EC50 =43.52 µg/mL in DPPH assay and tartaric acid aqueous bark extract with 30.69% of inhibition in TBRAS assay). Citric acid aqueous leaf extract (CALE) demonstrated 17.08% of the protective activity against CCl4-induced hepatoxicity in HepG2 cells (p < 0.05). CALE was standardized in order to assess its potential hepatoprotective effects against a mouse model of paracetamol-induced liver injury. The extract was administered orally to the animals at two different dosage levels (200 and 400 mg/kg b.wt.). For a duration of one week, the dosage was administered once daily. By improving the blood levels of biochemical, AOL demonstrated a notable dose-dependent hepatoprotective effect. The action of the standardized AOL was found to be similar to that of silymarin. AOL collected in Vietnam has a lot of potential to become a traditional medicine source.